Influence of the Location of Ascorbic Acid in Walnut Oil Spray-Dried Microparticles with Outer Layer on the Physical Characteristics and Oxidative Stability - Denisse Cáceres; Begoña Giménez; Gloria Márquez-Ruiz; Francisca Holgado; Cristina Vergara; Patricio Romero-Hasler; Eduardo Soto-Bustamante; Paz Robert (Antioxidants, 2020)
Purified walnut oil (PWO) microparticles with Capsul® (C, encapsulating agent), sodium alginate (SA) as outer layer and ascorbic acid (AA) as oxygen scavenger were obtained by spray drying using a three-fluid nozzle. AA was incorporated in the inner infeed (PWO-C(AA)/SA), in the outer infeed (PWO-C/SA(AA)) and in both infeed (PWO-C(AA)/SA(AA)). PWO-C(AA)/SA (4.56 h) and POW-C(AA)/SA(AA) (2.60 h) microparticles showed higher induction period than POW-C/SA(AA) (1.17 h), and lower formation of triacylglycerol dimers and polymers during storage (40 °C). Therefore, AA located in the inner infeed improved the oxidative stability of encapsulated PWO by removing the residual oxygen. AA in the SA outer layer did not improve the oxidative stability of encapsulated PWO since oxygen diffusion through the microparticles was limited and/or AA weakened the SA layer structure. The specific-location of AA (inner infeed) is a strategy to obtain stable spray-dried polyunsaturated oil-based microparticles for the design of foods enriched with omega-3 fatty acids.